Production of Bioethanol from Kepok Banana Peels (Musa acuminata x Musa balbisiana) using Different Types of Yeast - Lukhi Mulia Shitophyta; Rizka Septiana Zhirmayanti; Hasna Aeska Khoirunnisa; Shinta Amelia; Fatima Rauf (Universitas Islam Raden Rahmat, Malang, 2023)
Banana peels belong to lignocellulosic substrates, which can be used as raw material for bioethanol. Yeast plays an essential role in bioethanol fermentation. The study aims to compare ethanol yield using two different yeasts: Saccharomyces cerevisiae and Rhizopus oryzae, with yeast concentrations of 2, 3, and 5 g/L. The fermentation is run at room temperature for 120 hours. Results show that R. oryzae generates higher ethanol compared to the yeast of S. cerevisiae. Yeast of 2 g/L obtains the highest yield of ethanol. Yeast concentrations do not affect bioethanol production (p > 0.05).